(untitled) (GESTIÓN Y TENDENCIAS, 2024)
This article analyzes the impact of Chile’s 2014 insolvency reform (Law No. 20,720) compared with the previous 1982 regime. The authors argue that the old rules had an excessively "liquidation-oriented" focus and lengthy proceedings, which proved inefficient. The introduction of Law No. 20,720 marked a paradigm shift by encouraging the reorganization of viable firms and professionalizing key roles such as the reorganization supervisor (veedor) and the liquidator, as well as creating the Superintendency of Insolvency and Re-entrepreneurship. Analysis of World Bank data shows notable quantitative improvements: Chile’s Resolving Insolvency Score rose significantly, exceeding the Latin American average, and the Recovery Rate for creditors grew from 31 to 45 cents on the dollar between 2013 and 2019. The study nevertheless identifies persistent challenges. Despite these improvements, processing times for reorganizations increased until 2018 before stabilizing above 2014 levels, and there is high volatility in the success of reorganization agreements. Finally, the article notes that the Chilean system remains less attractive to secured creditors than developed economies and some regional peers, suggesting the need for specialized courts.